Tindak Tutur pada Interaksi Guru dan Siswa dalam Pembelajaran Bahasa Indonesia Kelas VIII di SMPN 5 Bengkulu Tengah - Rimadona, Firda; Wulandari, Catur; Yulistio, Didi (Jurnal Korpus, 2025)
Speech acts in learning are important because they are a means to educate, guide, and facilitate interaction between teachers and students. Forms of speech acts have contextual meanings aimed at understanding the meaning conveyed by the teacher. The purpose of this research is to describe the forms of locutionary, locutionary, and perlocutionary speech acts in the interaction between teachers and students in learning Indonesian by 18th grade students of SMPN 15 Bengkulu Tengah. This research uses a descriptive method with a qualitative approach. The data sources are teachers and students of class VIII of SMPN l5 lBengkulu lTengah. The data collection technique uses observation and documentation techniques. The researcher uses a research instrument in the form of a speech act classification table based on an observation table containing categories or outlines of research data and documentation in the form of audio visual recordings of teacher interactions with students in the classroom. Then the data analysis uses the following stages: recording, recording, coding, grouping data, analyzing, and presenting conclusions. The results of the study show that: (1) The locutionary speech acts that appear are in the form of notification speech. Without any intention or purpose in the communication, it is only for telling a story or simply informing. (2) The locutionary speech acts are of five types that were studied, including expressive, declarative, expressive, directive, and commissive. l As for locutionary speech acts, the dominant form of the locutionary act appears in the form of an opinion-expressing function, in the locutionary speech act, the dominant form of the locutionary act appears in the form of a prohibiting function, in the locutionary speech act, the dominant form of the locutionary act appears in the form of annoyance function, in the locutionary speech act, the dominant form of the locutionary act appears in the form of a commanding function, and in the locutionary speech act, the dominant form of the locutionary act appears in the form of a threatening function; and l (3) Perlocutionary speech acts aim to influence the speech interlocutor and have an effect. In this research, the perlocutionary speech acts that emerge are not only in the form of utterances but also actions in the form of movements of the teacher's body parts as signals that can be directly understood by students.